2013
DOI: 10.1371/journal.pone.0057828
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with 670 nm Light Up Regulates Cytochrome C Oxidase Expression and Reduces Inflammation in an Age-Related Macular Degeneration Model

Abstract: Inflammation is an umbrella feature of ageing. It is present in the aged retina and many retinal diseases including age-related macular degeneration (AMD). In ageing and in AMD mitochondrial function declines. In normal ageing this can be manipulated by brief exposure to 670 nm light on the retina, which increases mitochondrial membrane potential and reduces inflammation. Here we ask if 670 nm exposure has the same ability in an aged mouse model of AMD, the complement factor H knockout (CFH−/−) where inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 48 publications
8
128
1
1
Order By: Relevance
“…There appears a threshold of positive effects; cells need a certain level of NIr exposure to stimulate ATP production [12,13] and generate beneficial effects but after that level is reached, these benefits subside [9]. This is perhaps why several studies have indicated that NIr treatment is just as effective, if not more so, when applied in short bursts (ie pulses) than when applied continuously [12,18,38,39]. For Parkinson's disease patients, their treatment regime may include short but regular applications of NIr, rather than one continuous exposure [11].…”
Section: Neuroprotection By Nir Treatment Was Dose-dependentmentioning
confidence: 99%
“…There appears a threshold of positive effects; cells need a certain level of NIr exposure to stimulate ATP production [12,13] and generate beneficial effects but after that level is reached, these benefits subside [9]. This is perhaps why several studies have indicated that NIr treatment is just as effective, if not more so, when applied in short bursts (ie pulses) than when applied continuously [12,18,38,39]. For Parkinson's disease patients, their treatment regime may include short but regular applications of NIr, rather than one continuous exposure [11].…”
Section: Neuroprotection By Nir Treatment Was Dose-dependentmentioning
confidence: 99%
“…10] which reflect this region's more northerly latitude position on the planet, the results do nonetheless suggest that a reduced presence of VIS Red and NIR light during the winter period could be exacerbating dementia rates due to a temporary decrease in cytochrome c oxidase production. Moreover, despite the theoretical likelihood that MIR/FIR saunas should help to substitute for sunshine losses during winter months to regenerate TOSH, and thus by extension boost both glutathione and one of the copper portions of cytochrome c oxidase levels (Begum et al 2013), in the case of the most northerly of these countries where sauna use is more prevalent, sauna use does not seem to have much of a mitigating effect when one examines both Table 2 and the Figure 6 scattergram results. This becomes even clearer when one considers that 99% of Finland's 5.3 million people take at least one sauna bath per week.…”
Section: Real World Epidemiological Comparisonsmentioning
confidence: 94%
“…Additional changes included increased expression of CS inhibitory factor, decay-accelerating factor (DAF) in Müller cells and a concomitant decrease in retinal CD59a (Faber et al 2012;Williams et al 2013). The relation between oxidative stress and CS proteins in Cfh −/− mice could be demonstrated by treating aged Cfh −/− mice with 670 nm light, which increased mitochondrial function and reduced inflammation in the retina (Begum et al 2013). …”
Section: −/−mentioning
confidence: 99%